1980
DOI: 10.2466/pr0.1980.46.1.307
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Adopted and Nonadopted Children

Abstract: 41 adopted and 2,991 nonadopted children were compared on a behavior problem checklist completed by teachers. Adopted youngsters exceeded their nonadopted peers in frequency of disorders, especially conduct problems but also personality problems and socialized delinquency. Incidence of personality problems increased for adopted children from kindergarten through eighth grade and increased and then declined for nonadopted children over the same period. Boys experienced more maladjustment than girls, and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
2
3

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 0 publications
3
26
2
3
Order By: Relevance
“…However, other studies have found significant differences between adopted and nonadopted children on a wide range of variables measuring social, emotional, behavioral, and cognitive functioning (Netherlands : Verhulst, Althaus, & Versluis-den Bieman, 1990a ;Norway : Andresen, 1992 ;Sweden : Bohman, 1970, 1971Bohman & Sigvardsson, 1979, 1990U.S.A. : Brodzinsky, Radice, Huffman, & Merkler, 1987 ;Brodzinsky, Schechter, Braff, & Singer, 1984 ;Lindholm & Touliatos, 1980 ;Sharma, McGue, & Benson, 1996, 1998Zill, 1985b).…”
Section: Introductionmentioning
confidence: 96%
“…However, other studies have found significant differences between adopted and nonadopted children on a wide range of variables measuring social, emotional, behavioral, and cognitive functioning (Netherlands : Verhulst, Althaus, & Versluis-den Bieman, 1990a ;Norway : Andresen, 1992 ;Sweden : Bohman, 1970, 1971Bohman & Sigvardsson, 1979, 1990U.S.A. : Brodzinsky, Radice, Huffman, & Merkler, 1987 ;Brodzinsky, Schechter, Braff, & Singer, 1984 ;Lindholm & Touliatos, 1980 ;Sharma, McGue, & Benson, 1996, 1998Zill, 1985b).…”
Section: Introductionmentioning
confidence: 96%
“…Pringle (1974) found that the illegitimate ones who had been adopted performed better on measures of physical, emotional, and mental development than their counterparts who still lived with unmarried mothers. As a group, researchers who have compared the psychological adjustment of adopted to nonadopted children not in psychological clinics have been split in their results (Lindholm & Touliatos, 1980). Roughly equal numbers have shown positive or negative adjustment by the adopted youngsters.…”
Section: Infertile Couples Who Adopt Become Fertilementioning
confidence: 99%
“…Research also suggests that adopted children are more likely to manifest various forms of acting-out behavior and/or conduct disorders than their nonadopted counterparts, especially aggressiveness, oppositional behavior, impulsivity, hyperactivity, and running away (Austad & Simmons, 1978;Brodzinsky, Radice, Huffman, & Merkler, 1987;Dalby, Fox, & Haslam, 1982;Fullerton, Goodrich, & Berman, 1986;Kotsopoulos et al, 1988;Lindholm & Touliatos, 1980;Menlove, 1965;Weiss, 1985). Furthermore, adoptees have been reported to manifest a higher incidence of personality disorders (Lindholm & Touliatos, 1980;Schechter, Carlson, Simmons, & Work, 1964;Simon & Senturia, 1966), but either no difference in or a lower incidence of psychotic disorders (Brinich & Brinich, 1982;Fullerton et al, 1986;Lindholm & Touliatos, 1980;Schechter et al, 1964;Weiss, 1985).…”
mentioning
confidence: 95%
“…Furthermore, adoptees have been reported to manifest a higher incidence of personality disorders (Lindholm & Touliatos, 1980;Schechter, Carlson, Simmons, & Work, 1964;Simon & Senturia, 1966), but either no difference in or a lower incidence of psychotic disorders (Brinich & Brinich, 1982;Fullerton et al, 1986;Lindholm & Touliatos, 1980;Schechter et al, 1964;Weiss, 1985).…”
mentioning
confidence: 95%